LITERATURE REVIEW: KNOWLEDGE AND ATTITUDE OF PREGNANT WOMEN TOWARDS VOLUNTARY COUNSELING AND HIV/AIDS EXAMINATION - Irnawati, Irnawati; Mulyanda, Sella Retno; Purwita, Eva; Gustiana, Gustiana (Journal of Midwifery and Community Health (JMCH), 2025)
Background: AIDS, or Acquired Immunodeficiency Syndrome, is the final stage of HIV (Human Immunodeficiency Virus) infection. HIV is a virus that attacks the immune system, particularly CD4 cells (a type of T cell), which are crucial in fighting infections. Over time, HIV can damage the immune system so that the body becomes very susceptible to disease. One of the transmissions of HIV/AIDS is from pregnant women to their children, which can be prevented by screening pregnant women, known as Voluntary Counseling and Testing (VCT) for HIV/AIDS. VCT HIV/AIDS is a service that offers voluntary HIV counseling and testing. This service is designed to find out HIV status safely, confidentially, and with support from appropriate counseling. The main purpose of VCT is prevention, early detection, and management of HIV/AIDS. Objective: This literature review aims to determine the influence of the knowledge and attitudes of pregnant women on VCT HIV/AIDS. Method: using a literature review method based on data from Google Scholar, PubMed, and Proquest. The criteria for selecting articles for review are those that meet the inclusion criteria. The search yielded 513 articles, which were then filtered, and ten articles were selected for review. Results: The 10 articles reviewed had the same goal, namely to determine the relationship between the knowledge and attitudes of pregnant women towards VCT HIV/AIDS Conclusion: Knowledge and attitudes of pregnant women influence the implementation of VCT for HIV/AIDS during pregnancy. Keywords: HIV prevention, early detection of HIV, AIDS treatment